STEM Teaching Materials Integrated With Arduino Science Journal For Biology Prospective Teachers - Nawawi Nawawi; Ivan Eldes Dafrita (JURNAL PENDIDIKAN SAINS (JPS), 2022)
One effort made by the Biology Education Study Program to provide 21st-century skills to prospective biology teacher-students is to teach STEM through STEM courses. This research covers the issue of developing innovative learning-based teaching materials and developing 21st-century competencies. The research design used in product development was referred to the Thiagarajan 4D development model, such as the define, design, develop, and disseminate stage. The research objective is to understand STEM learning materials based on Arduino Science Journal in improving prospective 21st-century biology teachers. In particular, to determine: (1) The level of validity of Arduino Science Journal-based STEM teaching materials in increasing 21st-century biology teacher candidates. (2) The levels of the practicality of STEM teaching materials based on the Arduino Science Journal to improve prospective 21st-century biology teachers. (3) The Effectiveness of Arduino Science Journal-Based STEM Teaching Materials in Improving the Learning Outcomes of Prospective 21st Century Biology Teachers. The data of research is the percentage value of the validity and practicality. The results of this study indicated that the Arduino Science Journal integrated STEM teaching materials developed, had satisfied the criteria of validity and practicality, and were used effectively in STEM learning.